The Effect of Understanding of Financial Literacy and Ease of Digital Payment on the Continuity of Msmes in the Digitalization Era - Pratama, Dela; Nurwani, Nurwani; Samri Juliati Nasution, Yenni (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
Understanding financial literacy is the ability to understand knowledge and skills in managing financial resources in order to improve welfare. Financial technology is a combination of financial service systems and technology that provides easy access to financial transaction processing for the public when using these financial applications. This study aims to examine the effect of understanding financial literacy and the ease of digital payments on the sustainability of MSMEs in the digitalization era for MSMEs in the Medan Tembung Sub-District. The research method is a quantitative descriptive study with a population of 157 MSMEs in the Medan Tembung Sub-District. Source of data obtained from primary and secondary sources. Data collection techniques through distributing questionnaires using a simple random sampling technique. The results of the T-test research show that understanding financial literacy has a positive and significant effect on the sustainability of MSMEs in the digitalization era, digital payments have a positive and significant effect on the sustainability of MSMEs. This shows that the performance of MSMEs will increase significantly if MSME actors continue to increase their understanding of financial literacy and ease of digital payments in order to realize business continuity, the results of the f-test show that understanding financial literacy and the ease of digital payments simultaneously have a significant effect. It means that simultaneously there is an influence of understanding financial literacy and ease of digital payments on the sustainability of MSMEs in the digitalization era.